Nomogram construction and survival analysis in T3N0M0 breast cancer: a SEER population-based analysis - Lizhi Teng; Zeyu Zhang; Juntong Du; Yuhan Dong; Weiyang Tao (Scientific Reports)
Abstract Breast cancer, a heterogeneous disease, is notable for its high morbidity, recurrence, and mortality. T3N0M0 is controversial in terms of clinical prognosis and therapeutic decision-making. We collected baseline and treatment information on patients with T3N0M0 between 2010 and 2015 from the Surveillance, Epidemiology, and End Results programme (SEER) database. Univariate analyses of clinicopathological characteristics were performed using the log-rank test, while variables that were statistically significant (p < 0.05) were included in multivariate analyses to identify prognostic risk factors included in the construction of nomograms. Receiver operating characteristic (ROC) curves, calibration curves and decision curve analysis (DCA) curves were applied to evaluate the nomogram. We obtained a total of 4,641 patient clinical characteristics from the SEER database. In T3N0M0 group, the overall survival (OS) for 3, 5 and 10 years was 87.1%, 79.5% and 71.6%, and breast cancer-specific survival (BCSS) was 92.0%, 88.1% and 85.3%, respectively. We ultimately identified eight variables (age, grade, surgery, radiation, chemotherapy, ER-status, PR-status, Her2-status) were associated with OS while seven variables (age, grade, surgery, radiation, chemotherapy, PR-status, Her2-status) were associated with BCSS. The nomogram was constructed based on independent prognostic risk factors, the area under the curve (AUC) values were well performed, the ROC curves, calibration curves and DCA curves all indicated that the nomogram had better clinical practicability. The current study provides a new clinical assessment tool for T3N0M0 breast cancer patients, as well as a reference for clinicians in selecting management decisions.